FROM CASH TO DIGITAL: CHANGES IN SHARIA MONEY AND THEIR IMPACT ON INDONESIA'S MONETARY STABILITY - Purnamasari, Diana Nur Indah; Setiawan, M Tri Handika Wahyu; Ilmiah, Vahimatul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
The development of digital payment systems in Indonesia, particularly through QRIS, electronic money (e-money), and BI-FAST, has changed people's transaction behavior and has the potential to influence monetary policy transmission. From an Islamic economic perspective, the digitization of sharia money must ensure compliance with sharia principles, consumer protection, and distributive justice. This study aims to explain how the transition from cash to digital payments impacts Indonesia's monetary stability through the money demand channel, money velocity, inflation, and interest rate transmission. The method used is qualitative explanatory research based on secondary data from the period 2019–2025 (official releases from Bank Indonesia, BPS, BIS, IMF, and the latest academic literature). The results of the study show that the digitalization of sharia money through the implementation of QRIS and sharia mobile banking services has expanded financial inclusion and strengthened the transparency and efficiency of the payment system. The Indonesian Monetary Stability Index for the 2019–2025 period tends to be stable, despite facing pressure due to the COVID-19 pandemic and other external shocks. The findings also indicate a positive relationship between the level of adoption of digital sharia money and increased monetary stability, through inflation control, exchange rate strengthening, and smooth monetary policy transmission. Thus, the transformation from cash to digital in the Islamic finance sector has the potential to become a strategic instrument for strengthening national economic resilience, provided it is supported by adaptive regulations, strict sharia compliance, and widespread digital financial literacy across all levels of society.